Individual Variability in Migration Timing Can Explain Long-Term, Population-Level Advances in a Songbird - Kevin C. Fraser; Amanda Shave; Evelien de Greef; Joseph Siegrist; Colin J. Garroway (Frontiers in Ecology and Evolution, 2019)
Migratory animals may be particularly at-risk due to global climate change, as they must match their timing with asynchronous changes in suitable conditions across broad, spatiotemporal scales. It is unclear whether individual long-distance migratory songbirds can flexibly adjust their timing to varying inter-annual conditions. Longitudinal data for individuals sampled across migration are ideal for investigating phenotypic plasticity in migratory timing programs, but remain exceptionally rare. Using the largest, repeat-tracking data set available to date for a songbird (n = 33, purple martin Progne subis), we investigated individual variability in migration timing across 7,000–14,000 km migrations between North American breeding sites and South American overwintering sites. In contrast to previous studies of songbirds, we found broad, within-individual variability between years in the timing of spring departure (0–20 days), spring crossing of the Gulf of Mexico (0–20 days), and breeding site arrival (0–18 days). Spring departure and arrival dates were fairly repeatable across years (depart r = 0.39; arrive r = 0.32). Fall migration timing was more variable at the individual level (depart range = 0–19 days; gulf crossing range = 1–15 days; arrive range = 0–24 days) and less repeatable, with fall crossing of the Tropic of Cancer being the least repeatable (r = 0.0001). In this first, repeat-tracking study of a diurnal migratory songbird, the high within-individual variability in timing that we report may reflect the greater influence of environmental and social cues on migratory timing, as compared to the migration of more solitary, nocturnally migrating songbirds. Further, large, within-individual variability in migration dates (0–24 days) suggest that advances in spring arrival dates with climate change that have been reported for multiple songbird species (including purple martins) could potentially be explained by intra-individual flexibility in migration timing. However, whether phenotypic plasticity will be sufficient to keep up with the pace of climate change remains to be determined.